Internet Sehat, Hebat, Dilingkungan SMKN 7 Medan - Mufida Khairani; Boni Oktaviana; N Nurjamiyah; Yessy Fitri Anisa Lubis (Jurnal TUNAS, 2021)
The young generation is the backbone of the Nation and the State ”is a term that we often hear everyday. The changes that occur in the social environment today require role models and examples that can lead our society to a better direction. Moreover, in this reform era, the younger generation is required to participate more in building Indonesian society. Technology is believed to be a tool of change. The results of these technological findings are then used in human life activities.